2019
DOI: 10.1111/jocn.15133
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of a nurse practitioner‐led phase two cardiac rehabilitation programme on attendance and compliance

Abstract: Aims and Objectives To evaluate the impact of a nurse practitioner‐led phase two cardiac rehabilitation and secondary prevention programme on attendance and compliance. Background Despite strong evidence for the benefits of cardiac rehabilitation, attendance/completion rates remain low. Nurse practitioner‐led services have been reported as more effective than physician‐led services at increasing patient adherence to evidence‐based recommendations. However, nurse practitioner‐led programmes are uncommon and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In the present study, the intervention improved exercise tolerance. This finding was consistent with the results of related studies that showed improved exercise tolerance [ 34 , 36 , 37 ]. The management planning method employed may explain the remarkable results.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the intervention improved exercise tolerance. This finding was consistent with the results of related studies that showed improved exercise tolerance [ 34 , 36 , 37 ]. The management planning method employed may explain the remarkable results.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, nurse-led trainings are readily available and flexible, which may improve the fidelity of nurses' program delivery and patient retention rates. However, there is no evidence regarding the impact of nurse-led interventions on participant retention rates (O'Toole et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Patient assessment involved taking a health history and conducting a physical assessment. For example, a cardiovascular physical assessment was done at nurse-led CVD clinics [14][15][16][17][18] that involved the assessment of vital signs, such as heart rate, respiratory rate, blood pressure as well as cardiac and peripheral vascular examination, [19][20][21][22] and current health status for patients undergoing open heart surgeries. [14] Furthermore, nurses in nurse-led CVD clinics obtained a history of symptoms before and after percutaneous coronary intervention [20] and assessed symptoms and complications of atrial fibrillation (AF).…”
Section: Resultsmentioning
confidence: 99%